PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH MOTIVASI INTRINSIK DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU MTS DI KECAMATAN WINONG KABUPATEN PATI - Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the effect of intrinsic motivation and ProfessionalCompetence on the performance of teachers in Winong Islamic Junior High School Patiregency moderated with organizational culture. The specific objectives of this study wasto examine the effect of intrinsic motivation and professional competence on theperformance of teachers who are moderated by the role of organizational culture. Theusefulness of this study is to clarify and extend previous research on the effect of intrinsicmotivation and professional competence on the performance of teachers who moderatedthe organizational culture.This study used a population of teachers in Winong Islamic Junior High SchoolPati regency much as 173 teachers. Sampling techniques in this study is non probabiltysampling with proporsional sampling method. The method used in this research is multipleregression with difference quasi moderation.Based on the results of the study can be summarized as follows intrinsicmotivation does not affect the performance of teachers, professional competence has apositive and significant affect the performance of the teacher, organizational culture has apositive and significant affect the performance of the teacher, the influence of intrinsicmotivation on teacher performance does not moderated by organizational culture, and theinfluence of professional competence on performance teachers does not moderated byorganizational culture.Keywords: intrinsic motivation , professional competence, organizational culture, performance teacher and moderation